The Simulation of The Propagation of Electromagnetic Waves Through a Material with Various Thicknesses Using Finite Difference Time Domain (FDTD) (International Journal of Scientific Research and Management (IJSRM), 2023)
A finite difference time domain method in one dimension (1D-FDTD) is employed to study the properties of the propagation of electromagnetic waves across a medium with finite thicknesses. In this paper, we simulated the propagation of a Gaussian pulse. Since we simulated in one dimension, the absorbing boundary condition (ABC) can be applied to minimize undesirable reflection which generated at the numerical boundaries. We also implemented total field / scattering field (TF/SF) to ensure the source propagated in only one direction. The analysis performed by inserting the object with both relative permittivity and permeability values higher than one decreased the pulse’s amplitude.